Coexistence in Post-Secular Society: From Solidarity to Plurality (“İslam mədəniyyətində birgəyaşayış təcrübəsi” mövzusunda beynəlxalq simpozium, 2022)
The term of solidarity was the main concept of 19th century sociological thought. Emerging as scientific study of society the sociology first aimed to determine the basis of coexistence in social life and its main conditions. The answer of classical sociologists was the solidarity – unity of worldviews of people that sharing the same social and cultural domain. Solidarity was considered the main value that holds society together and provides coexistence. Classical sociologists considered society as living organism that its different parts function together to achieve common ends in cooperation. This is the main assumption of functionalist sociological theories. They were seeking the constant structures and static patters of sociocultural system in the age of extreme changes of modernization. As example, two types of solidarity developed by Emile Durkheim: mechanical solidarity and organic solidarity. Mechanical solidarity is a form of integration of people that share common beliefs and values. And organic solidarity occurs in society that operate based on division of labor. In this type of domain every member of society depends on one another.The importance of solidarity is obvious in modernization sociology. However, the object of solidarity has been much discussed. The modernist thinkers considered the main values of modern age the rationality, secularity and idea of progress. They thought that society must integrate on basis of rationality or science. Afterwards rational worldview would entail secularization eventually.The modernism ideas have been widely criticized by many social scientists including some postmodernist philosophers. First, they objected to accept modern science as only legitimate form of knowledge. Second, innovations and changes of modernization prosses do not result necessarily in progress. Lastly, modernization need not lead to secularization unavoidably. In post-secular society religion has important roles and functions in private as well as in social life. In post-secular society the question is what kind of solidarity guarantee coexistence? Do modernization ideas provide the basis for solidarity in post-secular society?It is important to underline that the main feature of postsecular society is plurality of competitive ideas, beliefs and values. Thus, the solidarity in such a domain in term of unity of beliefs and values is impossible even undesirable as well. Plurality is not considered a bearing a burden for society, but it is a valuable in itself and worthy to maintain for benefits of society. As Zygmunt Bauman pointed out that the main tenets of modernity were freedom, equality and fraternity, but in postsecular society the freedom, diversity and tolerance are the main values. So, the diversity and plurality are the main features of post-secular society. And it is concluded that the core value to maintain the coexistence in post-secular society is tolerance to diversity.